From biportal to uniportal video-assisted thoracoscopic anatomical lung resection: A single-institute experience. Issue 40 (October 2016) - Chang, Jia-Ming; Kam, Kam-Hong; Yen, Yi-Ting; Huang, Wei-Li; Chen, Wei; Tseng, Yau-Lin; Wu, Ming-Ho; Lai, Wu-Wei; Gonzalez-Rivas, Diego
Abstract : Abstract: Our study sought to review our experience from biportal to uniportal video-assisted thoracoscopic surgery (VATS) major lung resection. Lessons we learned from the evolution regarding technical aspects were also discussed. We retrospectively reviewed patients who underwent VATS lobectomy or segmentectomies in Ditmanson Medical Foundation Chia-Yi Christian Hospital, Chia-Yi, Taiwan, during January 2012 and December 2014. Patient clinical profiles, surgical indications and procedures, postoperative course, and oncological parameters were analyzed and compared between the biportal and uniportal groups. A total of 121 patients were enrolled in this study with median follow-up of 19.5 ± 11.6 months for all patients and 22.5 ± 11.5 months for primary lung cancer patients. Operation time (146.1 ± 31.9–158.7 ± 40.5 minutes; P  = 0.077), chest drainage time (3.8 ± 3.3–4.4 ± 2.4 days; P  = 0.309), conversion to thoracotomy rate (2.2%–2.6%; P  = 0.889), and complication rate (15.6%–19.7%; P  = 0.564) were equal between the groups, whereas blood loss (96.7 ± 193.2–263.6 ± 367; P  = 0.006) was lower in the uniportal group. For lung cancer cases, there were no statistical differences in the histology, cancer staging, mediastinal lymph node dissection stations, numbers of dissected N1, N2, and overall lymph nodes between uniportal and biportal groups. Our preliminary data showed that uniportal VATS anatomical lung resection is as feasible, equally safe, and of comparative oncological clearance efficacy to biportal VATS.